Safeness and efficacy of 2-µm handheld thulium laser during microsurgical resection of supratentorial and infratentorial meningiomas: Experience of a single center - Andrés Sanz, Julio Alberto; Marrone, Salvatore; Cacciotti, Guglielmo; Carpineta, Ettore; Scavo, Carlo Giacobbo; Roperto, Raffaele; Iacopino, Domenico G.; Sufianov, Rinat; Safarov, Aidar; Sufianov, Albert; Mastronardi, Luciano (Frontiers in Surgery, 2022)
Aims: We performed a retrospective non-randomized study to analyze the results of microsurgery of intracranial meningiomas using 2μm -Thulium flexible hand-held laser fiber (Revolix jr). Methods: From February 2014 to December 2021, 75 non-consecutive patients suffering from intracranial meningiomas have been operated on with microsurgical technique in our Department, assisted by 2μm -Thulium flexible hand-held laser. We have reviewed demographic and clinical data to evaluate safety and efficacy of the technique. Results: There was no complications related to the use of the 2μm -Thulium laser. We operated on a high percentage of cranial base, tentorial and posterior fossa meningioma in our series. Neurological outcome and degree of resection did not differ from previous series. Neurosurgical team found it easy to use and practical for avoiding bleeding and traction. Conclusions: The use of 2μm-Thulium-fiber hand-held flexible laser in microsurgery of intracranial meningiomas seems to be safe and to facilitate tumor resection, especially in ‘‘difficult’’ conditions (e.g., deep seated, highly vascularized and hard tumors). Even if in this limited retrospective trial the good functional outcome following conventional microsurgery had not further improved, nor the surgical time reduced by laser, focusing its use on ‘‘difficult’’ (large and vascularized) cases may lead to different results in future.